If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 23 = -3(2x + -1) Reorder the terms: 23 + 2x = -3(2x + -1) Reorder the terms: 23 + 2x = -3(-1 + 2x) 23 + 2x = (-1 * -3 + 2x * -3) 23 + 2x = (3 + -6x) Solving 23 + 2x = 3 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 23 + 2x + 6x = 3 + -6x + 6x Combine like terms: 2x + 6x = 8x 23 + 8x = 3 + -6x + 6x Combine like terms: -6x + 6x = 0 23 + 8x = 3 + 0 23 + 8x = 3 Add '-23' to each side of the equation. 23 + -23 + 8x = 3 + -23 Combine like terms: 23 + -23 = 0 0 + 8x = 3 + -23 8x = 3 + -23 Combine like terms: 3 + -23 = -20 8x = -20 Divide each side by '8'. x = -2.5 Simplifying x = -2.5
| 15-[3+7y-4(y+4)]=-4(3y-6)-[9(y-1)-15y+14] | | 3x-14x+25=2-6x-12 | | 36x-1=-8 | | 9+6x-8=6x+33-4x | | 3(m-8)=4(m+4) | | 25x^2+4=5 | | 4(8-x)-7-x=22 | | 4x-3=-0 | | 2(6ax+y)=11ax-7y | | 0.2(6)+x=0.4(6+x) | | 11-9A-2A=5E-3A-2 | | 4u^2-8u+3=0 | | -3y+7.4=20.9 | | 5X+9=11-5 | | .4x+.2(6)=x+6 | | 6x-(2x-4)=40 | | 4a-(5-a)=3(a+2) | | 6x^2+21x-15=0 | | 9x^2-81=12 | | 0.43=in(y) | | 4/7=m/9 | | (-144)-7x-4y=28 | | 2-7x=-7 | | -7x-4y=28(-144) | | .9x+.25(70)=.8(x+70) | | W=J+Jrt | | 2x^2-200=0 | | 5-5[4-(3y-2)]= | | 5x^2+11x+4=0 | | .33x=29 | | 16xy=52 | | 37c+45=0 |